Pathological nociceptors in two patients with erythromelalgia-like symptoms and rare genetic Nav 1.9 variants - Kleggetveit, Inge Petter; Schmelz, Martin (Brain and behavior, 2016)
Introduction The sodium channel Nav 1.9 is expressed in peripheral nociceptors and has recently been linked to human pain conditions, but the exact role of Nav 1.9 for human nociceptor excitability is still unclear. Methods C-nociceptors from two patients with late onset of erythromelalgia-like pain, signs of small fiber neuropathy, and rare genetic variants of Nav 1.9 (N1169S, I1293V) were assessed by microneurography. Results Compared with patients with comparable pain phenotypes (erythromelalgia-like pain without Nav-mutations and painful polyneuropathy), there was a tendency toward more activity-dependent slowing of conduction velocity in mechanoinsensitive C-nociceptors. Hyperexcitability to heating and electrical stimulation were seen in some nociceptors, and other unspecific signs of increased excitability, including spontaneous activity and mechanical sensitization, were also observed. Conclusions Although the functional roles of these genetic variants are still unknown, the microneurography findings may be compatible with increased C-nociceptor excitability based on increased Nav 1.9 function.
Gesehen am 10.07.2019